The association between leisure-time physical activity and cardiorespiratory and muscular fitness and job strain—Study with a Northern Finland birth cohort of 1966 - Kiema-Junes, Heli; Saarinen, Aino; Korpelainen, Raija; Ala-Mursula, Leena; Niemelä, Maisa; Farrahi, Vahid; Hintsanen, Mirka (John Wiley & Sons Ltd., 2025)
Job strain is a major concern in the workplace. Work-related stress is an increasing challenge worldwide as it is the leading cause of long-term sickness absences, disability pensions and lower productivity. Rarely studied simultaneously, both leisure-time physical activity (LTPA) and physical fitness (PF), which comprises cardiorespiratory fitness (CRF) and muscular fitness (MF), may have potential in preventing and managing job strain. The current study aimed to investigate whether LTPA, CRF and MF predict perceived job strain. In addition, the study examines reverse associations, that is, whether job strain predicts LTPA, CRF and MF. We used longitudinal population-based data from a Northern Finland birth cohort of 1966 (n = 5363) to analyse LTPA, CRF and MF as well as job strain and its components, job demands and job control, at age 31 years (1997) and 46 years (2012). Leisure-time physical activity was measured with a self-reported questionnaire whereas CRF and MF were measured as part of clinical examination. Linear regression analyses were used to analyse the data. In both men (n = 2548) and women (n = 2815), higher baseline MF predicted lower job strain and job demands 15 years later. In women, higher baseline total LTPA predicted higher job demands, whereas in men, higher CRF predicted lower job strain and higher job control. These associations remained significant, also when adjusted for education and occupational status. In the analyses on reverse associations, higher job control and higher job demands were linked to higher leisure-time moderate-to-vigorous physical activity (MVPA) and total LTPA 15 years later among both men and women, except for the association between job demands and total LTPA among women. These associations remained significant after adjustment for education and occupational status, except for the association of job control with MVPA and total LTPA among men. The association of higher job demands and total LTPA became significant in women. We conclude that LTPA and PF seem ...